Akibat Hukum Wanprestasi Atas Perjanjian Sewa Menyewa - Monicke Cintyara (Wajah Hukum, 2023)
This study aims to determine the legal consequences arising from the lease agreement. In resolving disputes related to lease agreements, one of these things can arise with the background of an authentic deed. An authentic deed is drawn up before an authorized official where the authorized official in this lease agreement is a Notary. The law does not distinguish in detail how to resolve legal disputes specifically regarding authentic deed of leasing agreements in which the contents of an agreement cannot be fulfilled by one of the parties who bind themselves. This writing aims to find out what the legal consequences arise from default disputes on lease agreements and find out how legal remedies can be taken by the parties, both tenants and lessees who feel disadvantaged because one party commits an act of default. In this study the authors used normative legal research methods. The conclusion that can be drawn in this study is what are the legal consequences arising from defaults committed by one of the parties to the lease agreement where one of the parties is harmed by the default, therefore the injured party can demand the fulfillment of his achievements as what has been agreed in the agreement and accompanied by compensation for losses to parties who are harmed by default. Against legal remedies that can be done is to make legal efforts that are in the law through litigation and non-litigation legal remedies.